(untitled) (Web of Teachers: Inderscience Research, 2023)
The creative abilities of students in pedagogical and psychological basis of improving the article will be discussed. Pedagogical conditions that help to develop the abilities of students, including motivational, constructive, communicative and organizational conditions will recommend. In the article is that creativity is a skill that can be applied in any professional activity in general and modern educational tools, as well as the need for the development and training of using the creative tasks is stressed.